Phylogeny and antibiotic resistance of Treponema pallidum subsp. pallidum - Nosov N.Yu.; Obraztsova O.A.; Katunin G.L.; Plakhova K.I.; Solomka V.S. (Клиническая микробиология и антимикробная химиотерапия, 2023)
The species Treponema pallidum includes 4 subspecies. According to the bioinformatic analysis, the syphilis pathogen T. pallidum subsp. pallidum was probably separated from the causative agents of yaws, bejel, and pinta more than 800 years ago. Its entry into Europe with its subsequent epidemic at the end of the 15th century remains a matter of debate. The rapid spread in the European countries and the increase in the incidence of the disease were most likely due to the significant genomic rearrangements, which increased the infectivity and virulence of the microorganism, as well as the sociocultural factors of that era. Currently, T. pallidum subsp. pallidum divides into 2 phylogenetic lines – SS14 and Nichols. The SS14 line is widespread and dominant in almost all countries; however, it is significantly inferior to the Nichols line in genetic diversity. Despite these facts, Nichols strains continue to be used in scientific laboratories as reference strains, which is obviously a disadvantage in research planning. While penicillin sensitivity remains, there is a significant spread of resistance of syphilis pathogen to macrolides, especially among SS14 isolates. Further studies of genetic variability as well as the structure of T. pallidum subsp. pallidum outer membrane proteins can bring modern medicine closer to the creating a vaccine against syphilis.